EFEKTIVITAS PENGELOLAAN LIMBAH MEDIS RUMAH SAKIT TERHADAP DAMPAK LINGKUNGAN HIDUP - Putri, Anggreany Haryani (KRTHA BHAYANGKARA, 2018)
The hospital is where the health services are operated and maintained with the utmost regard for the building and environmental hygiene aspect both physically, waste, liquid waste, clean water and insect/pest animals.Akantetapi to create the hygiene in hospitals is an attempt which is quite difficult and complex nature of the dealing with various aspects of, among others, culture/society behaviors, habits, environmental conditions, social and technological. Hospital waste is any waste generated by the activities of the hospital and other supporting activities.Hospital waste, in particular the infectious medical waste that has not been in the manage well will be catastrophic for the environment.Many hospitals have yet to manage infectious wastes according procedural should be.Not rare cases medical and non medical waste mixed giving rise to the problem of medical waste. Hospital waste processing can be done in various ways, by giving priority to sterilization, namely in the form of a reduction in volume, the use of sterilization must return with the first, recycling and processing.The most important thing in the processing of waste is the separation of waste, waste storage, handling of waste and waste disposal must be in accordance with the provisions of the regulations.So as not to give a negative impact to the environment.